Improving HSAPO‐34 Methanol‐to‐Olefin Turnover Capacity by Seeding the Hydrocarbon Pool. Issue 4 (5th January 2018) - Bollini, Praveen; Bhan, Aditya
Abstract: Seeding the hydrocarbon pool before exposure to methanol ensures the presence of active olefinic and aromatic chain carriers in the HSAPO‐34 cavity before the first methanol‐to‐olefin turnover. The primordial hydrocarbon pool enables the introduction, at low turnover numbers, of chain propagation steps that compete with methanol transfer dehydrogenation‐mediated chain termination steps, thereby increasing the fraction of converted methanol used for productive turnovers during methanol‐to‐olefin catalysis over HSAPO‐34. Seeding the hydrocarbon pool results, concurrently, in higher light‐olefin yields and lower rates of carbon loss. The increasing relative preponderance of methanol transfer dehydrogenation steps with increasing methanol pressure renders seeding more effective at higher methanol pressures. Under the conditions used in this study, seeding appears to accelerate the buildup of the hydrocarbon pool without significantly altering its composition. The results reported here outline a strategy for mitigating the deleterious effects of methanol transfer dehydrogenation reactions while reemphasizing their primacy in effecting catalyst deactivation during methanol‐to‐olefins conversion. Abstract : Seeding is believing : Controlled introduction of methanol‐to‐olefins conversion chain carriers into the HSAPO‐34 cavity before the first turnover is shown to simultaneously accelerate the buildup of the hydrocarbon pool and inhibit methanol transfer dehydrogenation events responsible for catalyst deactivation without altering the speciation of active chain carriers constituting the hydrocarbon pool.